2005
DOI: 10.1097/01.ju.0000148363.41998.d2
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Followup of Hand Assisted Laparoscopic Nephroureterectomy for Urothelial Carcinoma:: Factors Associated With Outcomes

Abstract: HALS nephroureterectomy is associated with 3-year outcomes that are strongly associated with stage and grade. We prefer the endoscopic cuff method for the distal ureter because it is performed after nephrectomy, does not require patient repositioning and is expedient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 18 publications
0
24
2
1
Order By: Relevance
“…Wolf and colleagues [86] published intermediate outcomes for HALNU. They demonstrated CSS rates of 94%, 86%, and 80% at 1, 2, and 3 years, respectively.…”
Section: Laparoscopic Nephroureterectomymentioning
confidence: 98%
“…Wolf and colleagues [86] published intermediate outcomes for HALNU. They demonstrated CSS rates of 94%, 86%, and 80% at 1, 2, and 3 years, respectively.…”
Section: Laparoscopic Nephroureterectomymentioning
confidence: 98%
“…[89][90][91][92][93] Several studies have attempted to identify potential risk factors for the development of subsequent bladder tumors; unfortunately, the collective data show marked heterogeneity in identifiable risk factors, which include pathologic stage, multifocality of the upper-tract lesion, female gender, incomplete distal ureterectomy, and a prior history of bladder tumors. [89][90][91][92][93][94] The lack of consensus presumably reflects different surgical techniques, management strategies, and surveillance regimens used in the management of this disease. Raman and colleagues reported that, following definitive surgical resection of upper-tract TCC (nephroureterectomy or segmental ureterectomy), bladder tumors developed in 44% of patients at a mean follow-up duration of 13.9 months; 95 60% of these bladder tumors were superficial low-grade lesions.…”
Section: Bladder Cancer Following Upper-tract Tccmentioning
confidence: 98%
“…10 Flexible office cystoscopy was done 3 months later as the first bladder tumor surveillance with subsequent cystoscopies at variable intervals.…”
Section: Hand Assisted Laparoscopic Nuxmentioning
confidence: 99%
“…6 Groups at some high volume centers have produced 5-year survival curves comparing NUx and endoscopic management. 7,8 In 2003 9 and 2005 10 we reported our results of endoscopic management and hand assisted laparoscopic NUx for UTUC with a mean followup of 15.8 months and a median followup 2148 www.jurology.com of 25.0, respectively. We now update these 2 cohorts with a median followup exceeding 6 years in survivors and with additional data allowing stratification by tumor characteristics and patient comorbidity to inform the comparison of long-term outcomes.…”
mentioning
confidence: 94%